An exploration of recovery among persons with severe mental health conditions in South Africa - Gamieldien, Fadia (Department of Psychiatry and Mental Health, 2025)
Background Severe mental health conditions have long-term impacts on multiple stakeholders, especially in low- and middle-income countries. Historically, public mental health services have focused on symptom reduction, emphasising clinical recovery. However, personal recovery, which considers mental health service users' lived experience, has received little attention. Since contextual factors influence outcomes, understanding and measuring recovery in low-resource settings is crucial. This study sought to explore personal recovery from severe mental health conditions in South Africa, where challenges, including poverty, stigma, and limited mental health resources intersect to shape the recovery process. Aim and objectives The overarching research question underpinning the thesis was: What constitutes and facilitates recovery for persons living with severe mental health conditions in South Africa? I aimed to answer this question and contribute to closing the research gap by pursuing four research objectives: (i) To conduct a scoping review on how personal recovery is conceptualised for persons living with severe mental health conditions in low- and middle-income countries; (ii) To explore and describe service provider perspectives on what recovery is for persons with severe mental health conditions in South Africa; (iii) To explore and describe what recovery is for men with severe mental health conditions and their caregivers in South Africa; and (iv) To evaluate the psychometric properties of the Recovery Assessment Scale among persons with severe mental health conditions in South Africa. Methods This mixed-methods study included both qualitative and quantitative components. Initially, a scoping review was undertaken to explore how recovery from severe mental health conditions is conceptualised and facilitated in low- and middle-income countries. Ten articles were included and thematically analysed. Next, semi-structured interviews and focus groups were conducted with 17 service providers in the Western Cape. This qualitative phase also included interviews with four male mental health service users and three of their caregivers. Visual participatory methods such as photovoice and life graphs were used to collect data. Finally, a quantitative evaluation was conducted to assess the psychometric properties of the Recovery Assessment Scale among 250 South African mental health service users. Results The scoping review revealed that recovery from severe mental health conditions is perceived as a continuous, non-linear process. While high-income countries focus on autonomy and independence, low- and middle-income countries emphasise social ii connectedness and spirituality as key recovery elements. Service providers suggested that clinical recovery models dominate mental health care, but personal recovery requires an approach that addresses social, economic, and cultural inequalities. For mental health service users, long-term relational support was vital to recovery. Even though spirituality was crucial to recovery, stigma from faith-based communities sometimes hindered access to spiritual support. Finally, the psychometric evaluation of the Recovery Assessment Scale showed a five-factor structure, with “Empowerment and Inner Strength” emerging as a new factor. The adapted Recovery Assessment Scale demonstrated strong internal consistency and reliability, proving a suitable tool for measuring recovery in South Africa. Discussion and conclusion The findings were synthesised into the Recovery Mandala, which identifies seven interconnected elements central to recovery from severe mental health conditions in South Africa: Collaborative Co-creation, Person-Centeredness, Hope and Empowerment, Social Network Utilisation, Caregiver Involvement, Spirituality and Religion, and Employment. These elements reflect the relational and holistic nature of recovery